[KCPR Fundraising] Auction. (Left to right): Stacey, Kate, Carlos, Justin, [Alex Woolery], and Sasquatch (2003)
KCPR fundraising auction event from circa 2003 (year based on when DJ Sasquatch was documented in the student newspaper). Three students sit around microphones, on air, while other KCPR staff work around them and eat Backstage Pizza. The photo was taken in Studio B (or the News Room) at KCPR when it was located in Room 201 in the Graphic Arts Building.